COMMUNITY WELFARE AND FOREST SUSTAINABILITY IN SOCIAL FORESTRY PROGRAMS: A CASE STUDY OF KTH BHAKTI ALAM LESTARI IN MALANG, EAST JAVA - Ramadhan, Ramli; Afiq, Muhammad D; Anggara, Arik; Triwanto, Joko (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
The implementation of the Social Forestry (SF) program in Indonesia has an important role in improving community welfare and promoting the sustainability of forest resources. The alignment of environmental conservation goals with initiatives aimed at improving community welfare can be achieved through the implementation of social forestry. Forest sustainability is considered to be in good condition when both ecological and economic objectives can be maintained. This study examined the level of welfare in Forest Farmers Group (KTH) Bhakti Alam Lestari through income contribution and forest sustainability. The results showed that the SF program provided an average contribution of 28.5% of total income. The welfare status of the KTH Bhakti Alam Lestari members was assessed based on the poverty line set by the Central Agency on Statistics Indonesia (BPS)2022. Based on this data, 54% of members of KTH Bhakti Alam Lestari are classified as underprivileged. SF management generates a monthly per capita income of 9,8 USD (IDR. 161,478). This has reduced the poverty rate to 20% of KTH members categorized as poor, and 80% classified as non-poor. Several efforts have been made to increase land cover, resulting in a decrease in open land classification from 19% to 15%, and an increase in low land cover classification from 25% to 32%, which was characterized by a greater diversity of plant species, especially from the recently planted MPTS plants on the farmers' land.